Comparison of mechanical behavior between conventional NiTi, CM, M-Wire and CM-EDM alloy instruments for cyclic fatigue and torsion fracture - evaluation of fracture surface in scanning electron microscope - Furlan, Renan Diego (2018)
The aim of this study was to evaluate the cyclic and torsional fatigue resistance of Nickel-Titanium rotary instruments manufactured by different thermal treatments. Were tested a total of 140 rotary instruments (n=20): Genius (GN size 25, .04 taper), Trushape (TS size 25, .06 taper), Logic (LOG size 25, .06 taper), Vortex Blue (VB size 25, .06 taper), ProTaper Gold (PTG size 25, .08 taper), Hyflex CM (HCM size 25, .06 taper) and Hyflex EDM (EDM size 25, .08 taper). Cyclic fatigue resistance testing was performed using an artificial stainless steel canal with a curvature (60° angle and 5- mm radius) located at 5 mm from the tip. The files (n=10) rotated until fracture and time was recorded in seconds. The torsional test evaluated the angular deflection and torque at failure of the instruments (n=10) at 3 mm from the tip according to ISO 3630- 1. The fractured surface of five instruments of each brand was observed by using scanning electron microscopy (SEM). Data were analysed using one-way ANOVA and Tukey tests, and the level of significance was set at 5%. The cyclic fatigue resistance value of EDM size 25, .08 taper was significantly higher than those of all instruments tested (P<0.05). The LOG size 25, .06 taper showed a higher cyclic fatigue resistance than those of GN size 25, .04 taper; TS size 25, .06 taper (P<0.05). There was no difference among the others groups. The torsional test showed that PTG size 25, .08 taper had the highest torsional strength value of all instruments tested followed by VB size 25, .06 taper and EDM size 25, .06 taper (P<0.05). The LOG size 25, .06 taper showed significant difference only with GN size 25, .04 taper (P<0.05). No difference was found among the others groups (P>0.05). In relation to angular deflection, the GN size 25, .04 taper; TS size 25, .06 taper; HCM size 25, .06 taper, and EDM size 25, .08 taper showed significantly higher values until fracture than the others groups (P<0.05). No difference was found among PTG size 25, .08 taper, LOG size 25, .06 taper, and VB size 25, .06 taper (P<0.05). The EDM size 25, .08 taper presented the highest cyclic fatigue resistance among all the tested instruments. For the torsional test, the PTG size 25, .08 taper showed highest torsional strength and lowest angular deflection values.